(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article considers the factors of human capital development and innovative analysis and several innovative approaches to its development. Also, new methods of providing employment to the population and young people who are not competitive in the labor market and various innovative methods of providing them with work in the labor market will be highlighted. We will also talk about the benefits provided by government.